Pengaruh Pendekatan Test Driven, Behavior Driven dan Model Driven terhadap Pengembangan Perangkat Lunak Metode Scrum - Waluyo, Prihadi Beny; Indriyanta, Gani; Tampubolon, Karel (Jurnal Terapan Teknologi Informasi, 2024)
This study examines the impact of integrating Test-Driven Development (TDD), Behavior-Driven Development (BDD), and Model-Driven Development (MDD) methodologies within the Scrum framework on the effectiveness and efficiency of software development. Through comprehensive literature analysis, this research explores how each methodology strengthens specific aspects of the Scrum process. TDD was found to enhance the reliability and accuracy of development with an emphasis on continuous testing, while BDD improves communication and collaboration among stakeholders by using clear and easily understandable language. MDD provides an efficient mechanism to address complex system designs through abstract models that are automatically converted into code. The findings indicate that the integration of these three methodologies significantly improves the quality and speed of development by leveraging the specific strengths of each methodology to optimize the development cycle in Scrum projects. The implications of these findings are relevant for practitioners engaged in Agile software development as well as academics interested in further research on development methodologies